The Concept of Normalization in Inclusive Early Childhood Education: An Examination of Bengt Nirje's Thoughts - Dewi Yunjiati; Ellen Prima (Journal of Education and Pedagogy, 2026)
This study aims to analyze the concept of normalization in the thought of Bengt Nirje and its relevance to inclusive early childhood education. The background of this study is grounded in the limited conceptual understanding of inclusion, which is often reduced to administrative aspects rather than being treated as a philosophical paradigm. This research employs a qualitative approach with a library research design, analyzing both primary and secondary sources relevant to the topic. Data analysis is conducted through content analysis combined with critical interpretation to generate a comprehensive understanding. The findings indicate that normalization emphasizes the provision of dignified, participatory, and meaningful living conditions for individuals with disabilities, rather than the standardization of individuals. In the context of inclusive early childhood education, this concept is relevant in promoting a more humanistic, flexible, and responsive learning environment that accommodates diversity. However, its implementation faces several challenges, including assumptions about normality, the risk of assimilation, as well as structural and cultural constraints. This study concludes that normalization retains its strategic value as a reflective framework in the development of inclusive education, provided that it is understood critically, contextually, and dialogically alongside contemporary approaches.